Opening Day for the South Bay Yacht Club - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees for the opening day of the South Bay Yacht Club in Alviso. This group is shown on the side of the club house for the South Bay Yacht Club.